2020
DOI: 10.1002/adom.201901421
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity‐Enhanced Blue Organic Light‐Emitting Diode for High‐Quality Monochromatic Light Source with Nonquarterwave Structural Design

Abstract: Despite their rapid development, organic light‐emitting diodes (OLEDs) are limited to display and lighting applications, and exploiting the application and development of OLEDs has become one of the critical issues. In this study, a new type of distributed Bragg reflector (DBR) with low absorption spacer as a bottom mirror is developed through nonquarterwave structural design. Different factors affecting the electroluminescence (EL) properties of microcavity OLEDs (MOLEDs) are investigated by using the optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In order to achieve the optimized resonance enhancement effect and device performance, we need to systematically design the thickness of each layer. Under the resonance condition, the emission enhancement factor Ge along the normal direction is given by [33,40,47] where R 1 and R 2 are the reflectivities of DBR and Al mirrors, respectively, 𝜉 is the antinode enhancement factor, 𝜏 cav and 𝜏 are the lifetimes of spontaneous emissions in resonant microcavity and free space. According to Purcell effect, the spontaneous emission rate of resonant photons is enhanced in microcavity, [53] but this effect is unobvious for planar microcavities.…”
Section: Optical Design and Simulation Of Mpeledmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to achieve the optimized resonance enhancement effect and device performance, we need to systematically design the thickness of each layer. Under the resonance condition, the emission enhancement factor Ge along the normal direction is given by [33,40,47] where R 1 and R 2 are the reflectivities of DBR and Al mirrors, respectively, 𝜉 is the antinode enhancement factor, 𝜏 cav and 𝜏 are the lifetimes of spontaneous emissions in resonant microcavity and free space. According to Purcell effect, the spontaneous emission rate of resonant photons is enhanced in microcavity, [53] but this effect is unobvious for planar microcavities.…”
Section: Optical Design and Simulation Of Mpeledmentioning
confidence: 99%
“…[47] On the contrary, microcavity exhibits the suppression of emission when the cavity mode is not in the range of natural spectrum. The integrated enhancement factor G int over all wavelengths is given by [33,40,47]…”
Section: Optical Design and Simulation Of Mpeledmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 122 ] Lin et al reported narrow‐band pure‐UV (FWHM ≈ 9.95 nm) and blue (FWHM ≈ 8 nm) electroluminescence from microcavity OLEDs using 1,2‐di‐ p ‐tolyl‐1H‐phenanthro[9,10‐d]‐imidazole (Tol‐PPI) and BSB‐Cz as emitters, respectively. [ 123 ]…”
Section: Typical Resonator Architecturesmentioning
confidence: 99%
“…
maximum (FWHM) and current efficiency (CE) of the TEOLEDs are significantly optimized owing to the micro-cavity effect of the top-emitting structure, promoting the applications in ultra-high-definition displays and micro-displays. [11,12] However, one major challenge of the TEOLEDs is the severe waveguide and plasmonic losses, which hinders the light outputcoupling and results in the low external quantum efficiency (EQE). [13,14] Introducing the localized surface plasmon resonance (LSPR) in the device is an effective way to increase the EQE of the OLEDs.
…”
mentioning
confidence: 99%